2013
DOI: 10.4049/jimmunol.1301604
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Apoptosis and Innate Immune Stimuli in Inflammation-Induced Preterm Labor

Abstract: An innate immune response is required for successful implantation and placentation. This is regulated in part by a2 isoform of V-ATPase (a2V) and the concurrent infiltration of M1 (inflammatory) and M2 (anti-inflammatory) macrophages to the uterus and placenta. The objective of present study was to identify the role of a2V during inflammation-induced preterm labor in mice and its relationship to the regulation of apoptosis and innate immune responses. Using a mouse model of infection-induced preterm delivery, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 66 publications
4
51
1
Order By: Relevance
“…84 Our study of macrophage phenotypes showed that during preterm labor induced by double hit of PGN1poly(I : C), increased the number of macrophages (F4/ 801) that were double-positive for CD11c and CD206. 26 Wentworth et al 85 has demonstrated these double positive CD11c…”
Section: Preterm Labor and Macrophage Phenotypesmentioning
confidence: 96%
See 4 more Smart Citations
“…84 Our study of macrophage phenotypes showed that during preterm labor induced by double hit of PGN1poly(I : C), increased the number of macrophages (F4/ 801) that were double-positive for CD11c and CD206. 26 Wentworth et al 85 has demonstrated these double positive CD11c…”
Section: Preterm Labor and Macrophage Phenotypesmentioning
confidence: 96%
“…We focused on one of the crucial enzyme which, in part, regulates innate response is Vacuolar ATPase (V-ATPase). 26 V-ATPase is a multisubunit enzyme which is responsible for regulating the acidic environment of intracellular organelles and the extracellular environment via ATP hydrolysis. Its expression in round spermatids was first demonstrated by Wada and colleagues.…”
Section: Seminal Fluid and Immune Response For Embryo Implantationmentioning
confidence: 99%
See 3 more Smart Citations